Capacity Development in a Participatory Adaptive Programme: the Case o f the Clarissa Consortium - Widmer, Mireille; Apgar, Marina; Afroze, Jiniya; Malla, Sudhir; Healey, Jill; Constant, Sendrine (Institute of Development Studies, 2022)
Doing development differently rests on deliberate efforts to reflect a nd learn, not just about what programmes are doing and achieving, but about how they are working. This is particularly important for an acti on research programme like Child Labour: Action- Research-Innovation i n South and South-Eastern Asia (CLARISSA), which is implemented by a c onsortium of organisations from across the research and development sp ectrum, during a rapidly changing global pandemic. Harnessing the pote ntial of diverse skills and complementary strengths across partners in responding to the complex challenge of the worst forms of child labou r, requires capacity to work together in novel ways. This Research and Evidence Paper documents how CLARISSA approached capacity development , and what we learnt from our challenges and successes. From the start , the programme incorporated a capacity development strategy resting o n self-assessment of a wide range of behavioural and technical compete ncies that were deemed important for programme implementation, formal training activities, and periodic review of progress through an after- action review (AAR) process. An inventory of capacity development acti vities that took place during the first year of implementation reveals a wide range of additional, unplanned activities, enabled by the prog ramme’s flexibility and adaptive management strategy. These are organi sed into eight modalities, according to the individual or collective n ature of the activity, and its sequencing – namely, whether capacity d evelopment happens prior to, during, or after (from) implementation. W e conclude with some reflections on the emergent nature of capacity de velopment. Planning capacity development in an adaptive programme prov ides a scaffolding in terms of time, resources, and legitimacy that su stains adaptiveness. We also recognise the gaps that remain to be addr essed, particularly on scaling up individual learning to collective ca pabilities, and widening the focus from implementation teams to indivi duals working at consortium level.